The effects of NAFTA on economic growth - Víctor Manuel Cuevas Ahumada; Roger Ivanodik Juan López Churata (Investigación Económica, 2019)
This paper evaluates the effects of the North American Free Trade Agreement on the economic growth of Mexico, the United States and Canada by means of an augmented Solow growth model. Such a model is estimated with panel data through two econometric methods: 1) the Arellano-Bond dynamic panel Generalized Method of Moments, and 2) Feasible Generalized Least Squares. The two techniques are consistent in indicating that trade raises Gross Domestic Product (GDP) per capita, controlling for physical capital stock per capita, human capital formation, total factor productivity, and the capital depreciation rate. However, the most important source of GDP per capita growth is human capital formation, which highlights the need to promote trade while investing more in long-term formal education, short-term training programs and the whole process of knowledge transferring.
Keywords: C51; F14; O47; 330; Economic growth; international trade; human capital formation; panel data models